(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Babu (1997) was conducted a study on the effects ofphysical exercises and yogic practices on selected physical and physiologicalvariables of college women students in Kerala. For the purpose of this study 90 college women students were selected assubjects randomly and their age was between 18 and 25 years. Further, they were divided into three equalgroups at random and they were called as physical exercise group, yogicpractice group and control group, yogic practice group and control group. Theselected physical variables such as speed and explosive power and physiologicalvariables such as pulse rate and breath holding time. The pretest was conductedfor the above variables for the three groups. The post test was conducted forthe above variables after six weeks of training. The first experimental group has undergone atreatment of selected physical exercise and second experimental group hasundergone the selected yogic practices for six weeks. The control group was notany of the training. ANCOVA was employed as a statistical technique. It was found out that the resting pulse rateand breath holding time were improved due to the influence of selected physicalexercise and yogic practices. It alsorevealed that the speed and leg explosive power were not improved due theinfluence of selected physical exercises and yogic practices. Further it was showed that there was nosignificant difference among the groups, namely, physical exercise group andyogic exercise group and there was no changes occurred in the control group.